Sistem Penjualan Barang Elektronik Dan Furniture Berbasis Web Pada Toko Bali Artha Jaya - Wijaksana, I Kadek Krisna; Wibawa, Kadek Suar; Susila, Anak Agung Ngurah Hary (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Bali Artha Jaya is a business engaged in the sale of electronic goods and furniture. The sales are carried out conventionally which is still depend on SPG or SPB and do not take advantage of technology. In order to increasing the sales, we need a website that is able to answer these problems. This study aims to design an e-commerce website to provide sales facilities. The data collected during the research were profile data, sales flow data, and product data sold. The design for making a website is obtained by using the Data Flow Diagram (DFD) technique. A table design is made which is equipped with fields that are implemented in a database application program. The data collection method used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). System testing was carried out using the Post-Study System Usability Questionnaire (PSSUQ) method. Based on the results of system testing, satisfaction data was obtained overall with an average score of 2.40 included in the lower limit (good) category. This value illustrates that the website websites that have been created is good or successful.